Organizational Performance in Public Organizations with Dynamic Capabilities as Mediation: The Influence of Strategy Implementation and Innovation - Fachriansyah, Muh Rizqi; Wahdiyat Moko; Sudjatno (Social Science Studies, 2024)
Research Aims: The main objective of this study is to investigate the impact of strategic implementation, innovation and dynamic capabilities on organizational performance. Design/methodology/approach: This research is included in the explanatory research category. The research was carried out in the Indonesian public organization PT.Pegadaian, located in the Malang city area, which covers all Services Branches (CP) and Branch Service Units (UPC). The sample for this research was 81 people including: Business Deputy, Head of Pawn and non-Pawn department, Branch Leader, Pawn and non-Pawn Manager, UPC Manager. The sampling method uses saturated sampling or census. Questionnaires were distributed using a 1-5 Likert scale measurement and statistical analysis (PLS-SEM) to analyze the data. Research Findings: Research findings show a relationship between strategy implementation and dynamic capabilities on organizational performance, then innovation does not have significant effects on Organizational Performance. Strategy implementation and innovation have significant effect on Dynamic Capabilities, and Dynamic Capabilities are able to mediate the influence between Strategy Implementation and innovation on Organizational Performance. Theoretical Contribution/Originality: This research provides new insights into how Strategy Implementation, Innovation, and Dynamic Capabilities influence employee Organizational Performance.